Experimental study on combustion and emission of an SI engine with natural gas/ethanol combined injection. (15th June 2022) - Zhao, Zhe; Huang, Yan; Yu, Xiumin; Guo, Zezhou; Yu, Longlong; Meng, Shuxuan; Li, Decheng
Highlights: In this paper, natural gas and ethanol are innovatively mixed in a dual-injection SI engine. In this paper, a combustion system of CNG direct injection plus ethanol port injection is built on a commonly used four-cylinder SI engine, and the optimal combination ratio of CDI+EPI is studied. 5%CDIr+95%EPIr can obviously increase the engine power performance and decline the gaseous emissions, and 135°-150°CA BTDC is an ideal DIT. Abstract: Pure ethanol spark ignition (SI) engines have poor fuel atomization and mixture formation at lower load. The objective of this study is to improve the performance of ethanol SI engines through dual-injection mode with ethanol port injection plus compressed nature gas direct injection (EPI + CDI). In this paper, the performance engine at different compressed nature gas direct injection ratio (CDIr) and DIT was studied at the speed of 1500rmp. The results show that, with the increase of CDIr or the delay of direct injection timing (DIT), torque, Pmax and NOx first increases and then decreases; CA 10–90, CoVIMEP, CO and particle number (PN) first decreases and then increases; HC keeps decreasing. When CDIr = 5%, DIT = 150°CA BTDC, CA 10–90 reaches the lowest value, which is about 6.21% lower than the original engine. Besides, under this operation condition, CoVIMEP decreases to 1.13%, which is about 18.72% lower than the original engine. It is worth noting that the higher torque and Pmax at this time indicate the better combustion in the cylinder, but NOx does not increase significantly. In addition, total particle number (TPN) also reaches the minimum at this time. When CDIr = 5%, 10%, 15% and 20%, HC is reduced by 11.42%, 13.53%, 20.05% and 23.26% on average. When CDIr ≤ 10%, the overall CO is lower than the original engine. In summary, EPI + CDI can not only effectively improve combustion, but also reduce emissions. The cooperation of 5%CDIr + 95%EPI + 150°CA BTDC DIT can form an effective stratified mixture in the cylinder, providing stable and promising performance. And it is the best direct injection strategy for CDI + EPI dual-fuel combined injection SI engine.